The French construction ‘j’arrive à + INF’ at the borders of modality. An exploratory survey of a journalistic corpus - Dell'Oro, Francesca (Alessandria: Dell'Orso, 2023)
The French construction j’arrive à + INF seems to allow readings very close to possibility modality. After a brief diachronic and typological description, I carry out an investigation of a journalistic corpus in order to better understand its contemporary uses. Subsequently, after having shown that it has implicative semantics, I claim that the construction is irreducible to modality, as it lacks the property of introducing non-factual states of affairs.
Keywords: corpus; French; implicative verbs; modality; verbs of motion